IMPLEMENTASI KURIKULUM MERDEKA DI SMP NEGERI 5 LUBUKLINGGAU; ANALISIS KESIAPAN GURU, TANTANGAN, DAN DAMPAKNYA TERHADAP PROSES PEMBELAJARAN - Ana Oswari; Danim, Sudarwan; Connie (UNIVERSITAS BENGKULU, 2025)
This study analyzes the implementation of the Independent Curriculum at SMP Negeri 5 Lubuklinggau, focusing on teacher readiness, challenges, and its impact on the learning process. The research subjects consist of the principal, teachers, and students who are directly involved in the curriculum implementation. This study employs a qualitative approach using a case study method. Data were collected through interviews, observations, and documentation, and analyzed using the Miles, Huberman, and Saldana model. The findings indicate that while teachers understand the theoretical concepts of the Independent Curriculum, they still face difficulties in preparing teaching modules, applying differentiated instruction, and conducting formative assessments. The main challenges include limited time, lack of practical training, and minimal mentoring. The positive impact observed includes increased student engagement and creativity, although the key challenges remain to be addressed. The study recommends practice-based training, direct classroom mentoring, and the strengthening of teacher communities.